4(z+2)-2z=10+3(z-3)

Simple and best practice solution for 4(z+2)-2z=10+3(z-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(z+2)-2z=10+3(z-3) equation:


Simplifying
4(z + 2) + -2z = 10 + 3(z + -3)

Reorder the terms:
4(2 + z) + -2z = 10 + 3(z + -3)
(2 * 4 + z * 4) + -2z = 10 + 3(z + -3)
(8 + 4z) + -2z = 10 + 3(z + -3)

Combine like terms: 4z + -2z = 2z
8 + 2z = 10 + 3(z + -3)

Reorder the terms:
8 + 2z = 10 + 3(-3 + z)
8 + 2z = 10 + (-3 * 3 + z * 3)
8 + 2z = 10 + (-9 + 3z)

Combine like terms: 10 + -9 = 1
8 + 2z = 1 + 3z

Solving
8 + 2z = 1 + 3z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-3z' to each side of the equation.
8 + 2z + -3z = 1 + 3z + -3z

Combine like terms: 2z + -3z = -1z
8 + -1z = 1 + 3z + -3z

Combine like terms: 3z + -3z = 0
8 + -1z = 1 + 0
8 + -1z = 1

Add '-8' to each side of the equation.
8 + -8 + -1z = 1 + -8

Combine like terms: 8 + -8 = 0
0 + -1z = 1 + -8
-1z = 1 + -8

Combine like terms: 1 + -8 = -7
-1z = -7

Divide each side by '-1'.
z = 7

Simplifying
z = 7

See similar equations:

| 2(x+7)=40 | | -3.5(4a+1.9)a= | | -3.5(4a+1.9)= | | 4(x-8)=80 | | 8x^2+8x^6= | | (2x+3)(2-3x)-(2-3x)(4x+1)=0 | | y=3x+5y | | xy=3x+5y | | 32v^4-2u^4v^4=0 | | 3(w+3)=2w-2 | | y=10x^2+20x-1 | | 4x^2-25+6=0 | | 3x^2+16x=0 | | 3.7x=4.81 | | 14-(3m+6)=2+2m-19 | | -3.3y=6.6 | | 2=5x-3y | | -3.1y=21.7 | | 28-9x=12-11x | | 14+2x=-8 | | 7x-y=14solvex | | 2(x+7)=-8 | | -26=-364 | | 67-2x=34x+15 | | 14-(x+9)=7x-3 | | 5x+35-6x=1-9x+2 | | 268v*5=345+32v | | 3x+7=123-10x | | 12+x=8 | | 0.5+b+4=2(b+2) | | X+0.5-3=4.5 | | mx^2+(2m-2)x+(m-1)=0 |

Equations solver categories